A micro-sized high-temperature thorium reactor with Duplex TRISO fuel with enhanced thorium utilization compared to the SBU configuration - Rabir M.H.; Ismail A.F.; Yahya M.S. (Elsevier Ltd, 2024)
This study offers a neutronisc core calculation to assess the potential of the compact microheterogeneous thorium-uranium TRistructural ISOtropic (TRISO) fuel design for the micro-modular high temperature reactor. The Duplex-fueled core and the Seed-and-Blanket-Unit (SBU)-fueled core were modelled and compared using the MCNPX 2.7 Monte Carlo code. The Th:U ratio and initial fissile mass of both cores were set to be the same. The dispersion of thorium and uranium in the Duplex-fueled core is more uniform compared to that in the SBU-fueled core. The study demonstrates that Duplex TRISO fuel offers both improved core power distribution uniformity and superior neutronic performance compared to SBU fuel in a core. The utilisation of a Duplex-fueled core leads to a 5 % higher core conversion ratio and resonance capture rate, which ultimately results in an extra long-term production of 233U. Additionally, its FTC value is lower. The required material and thickness of the neutron reflector, are also discussed, though only as a preliminary analysis. Nevertheless, the findings clearly demonstrate that the Duplex TRISO fuel design concept offers valuable flexibility and optimization in the distribution of fertile and fissile material mass. These characteristics are of utmost importance for the advancement of thorium reactors, as they significantly enhance neutronic performance. 2023 Elsevier Ltd